Saudi regime resilience after the 2011 Arab popular uprisings. Issue 1 (2nd January 2016) - Al-Rasheed, Madawi
ABSTRACT: Although all Arab monarchies (Gulf Cooperation Council countries, Jordan and Morocco) witnessed varying degrees of mass protest during the Arab uprisings of 2011, none of the kings and princes has thus far been deposed. The Kingdom of Saudi Arabia saw pockets of sporadic protest in many cities in the early months of 2011, but those failed to evolve into a mass protest movement across the country. This paper analyzes the conditions that led to Saudi stability, attributing it to a combination of domestic and regional factors. The paper also highlights how the conditions that led to monarchical resilience over the last five years may result in unexpected upheavals in the future.